Implementations of leadership in energy and environmental design (LEED) in RMG sectors of Bangladesh – a comparative study between the advantages and disadvantages of green approach - Alif, Munshi (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.